2021
DOI: 10.1111/and.14136
|View full text |Cite
|
Sign up to set email alerts
|

Absence of SARS‐CoV‐2 infection in the semen of men recovering from COVID‐19 infection: An exploratory study and review of literature

Abstract: The effect of COVID‐19 on the male reproductive tract has been sparsely studied. This exploratory study was designed to determine the presence of SARS‐CoV‐2 in the semen of men recovering from COVID‐19. A systematic literature review was also performed as per PRISMA guidelines to gather perspective on this topic. The prospective study included men 21 years and older recovering from COVID‐19 with nasopharyngeal swab negative for SARS‐CoV‐2 or at least two weeks from the last COVID RT‐PCR positivity. After clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Some studies have suggested the absence of SARS-CoV-2 RNA in semen samples of asymptomatic COVID-19-positive men or those suffering or recovering from mild COVID-19, even though they were still in the acute phase and positive for the virus in the nasopharyngeal swab ( Holtmann et al , 2020 ; Rawlings et al , 2020 ; Best et al , 2021 ; Burke et al , 2021 ; Guo et al. , 2021a ; Gupta et al , 2021 ; Ma et al , 2021 ; Paoli et al , 2021a ; Ruan et al , 2021 ; Scroppo et al , 2021 ; SharMa et al , 2021 ; Temiz et al , 2021 ; Donders et al , 2022 ; Fraietta et al , 2022 ; Huang et al , 2022b ; Pavone et al , 2022 ). Other authors reported the presence of SARS-CoV-2 in the semen and in the seminal plasma fraction (by PCR testing) in the acute phase and after recovery after mild and moderate COVID-19 in a limited percentage of patients, respectively, in 4/15, 1/6, 1/31, 1/19 and 6/38 cases ( Li et al , 2020a ; Delaroche et al , 2021 ; Machado et al , 2021 ; Purpura et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have suggested the absence of SARS-CoV-2 RNA in semen samples of asymptomatic COVID-19-positive men or those suffering or recovering from mild COVID-19, even though they were still in the acute phase and positive for the virus in the nasopharyngeal swab ( Holtmann et al , 2020 ; Rawlings et al , 2020 ; Best et al , 2021 ; Burke et al , 2021 ; Guo et al. , 2021a ; Gupta et al , 2021 ; Ma et al , 2021 ; Paoli et al , 2021a ; Ruan et al , 2021 ; Scroppo et al , 2021 ; SharMa et al , 2021 ; Temiz et al , 2021 ; Donders et al , 2022 ; Fraietta et al , 2022 ; Huang et al , 2022b ; Pavone et al , 2022 ). Other authors reported the presence of SARS-CoV-2 in the semen and in the seminal plasma fraction (by PCR testing) in the acute phase and after recovery after mild and moderate COVID-19 in a limited percentage of patients, respectively, in 4/15, 1/6, 1/31, 1/19 and 6/38 cases ( Li et al , 2020a ; Delaroche et al , 2021 ; Machado et al , 2021 ; Purpura et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, SARS-CoV-2 nucleic acid was not detected in any specimen by RT-PCR [ 64 ]. In the same line, many studies that assessed semen for the presence of SARS-CoV-2 during the recovery stage of COVID-19 in non-severe diseased men failed to detect the virus RNA using RT-PCR [ 14 , 65 , 66 , 67 , 140 ].…”
Section: The Impact Of Covid-19 On Male Fertility Explained: Facts Ev...mentioning
confidence: 99%